PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) MENGGUNAKAN QUIZIZZ DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Insan Kumila Riyadi; Dhina Cahya Rohim; Devy Aufia Abshor; Amalia Rahmawati; Moh. Aris Prasetiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the relationship between using the Numbered Head Together (NHT) learning model using Quizizz and the mathematics learning outcomes of class III students at SD 1 Undaan Kidul. This research uses a quantitative approach method with a quasi-experimental type. Data was collected through observation, interviews, documentation, and tests. The data collection technique in this research used pre-test and post-test questions given to two classes, namely class III A as the experimental class and class III B as the control class. In this research, researchers took a sample of 41 students from class III of SD 1 Undaan Kidul. Based on the normality test, shows that the data is normally distributed with results of 0.253 for the control class and 0.285 for the experimental class. The results of the analysis of hypothesis testing using the t-test obtained a Sig value. 0.004 < 0.05, it can be concluded that there is an influence of the Numbered Head Together (NHT)) learning model using Quizizz on the learning outcomes of class III elementary school students.